Evaluation of port efficiency in Shanghai Port and Busan Port based on three-stage DEA model with environmental concerns - Huang, Xiaoling; Wang, Yawei; Dai, Xiamei; Luo, Jack Xunjie; Chen, Jihong (Transport, 2020)
The global green development has led many ports to impose measures to reduce emissions and improve port efficiency. As large-scale construction can do damage to the environment, it is not supported under the green strategy, which makes it more important to make full use of existing resources in the port competition. While, whether there is a relationship between emissions and port efficiency, and whether the relationship can reflect the problems in port management are vital factors need to be considered when making port development strategy. To solve the two problems, this paper takes the case of Shanghai Port and Busan Port, and uses the three-stage Data Envelopment Analysis (DEA) to evaluate the efficiency of the two ports respectively. Pollutant emissions from the ports are selected as an environmental variable in the second stage to examine their effects on the redundancy of input variables. The results indicate that the efficiency of Shanghai Port is insufficient due to excessive scale and pollutant emissions. Based on the results, some suggestions are given to improve the drawbacks. Furthermore, the use of the three-stage DEA to study the annual change in performance of a single target in this paper is also a novelty.First published online 20 November 2019